Morphostructure of the western sector of the North Scotia Ridge - Esteban, Federico Damián (2010)
The North Scotia Ridge (NSR) is the submerged morpho-structural expression of the Scotia plate northern edge. It is constituted by the Tierra del Fuego continental margin, isla de Los Estados, Burdwood (BB), Davis and Aurora banks, and the Georgias islands shelf (Parker et al., 1996; Barker, 2001; Giner-Robles et al., 2003; Pandey et al., 2010). About 40 Ma these blocks were grouped forming a continental link between Tierra del Fuego and Antarctica. Afterwards, with the development of the Scotia plate, the blocks drifted towards the east to their actual position (Barker, 2001; Pandey et al., 2010). Several authors have established that the actual movement of the South America - Scotia plate boundary is left-lateral (Forsyth, 1975; Pelayo and Wiens, 1989; Giner-Robles et al., 2003; Thomas et al., 2003; Smalley et al., 2007). In the Tierra del Fuego region, the plate boundary is represented by a mostly transtensional fault system known as Magallanes-Fagnano (Lodolo et al., 2002, 2003, 2006, Tassone et al., 2008; Menichetti et al., 2008). Towards east, the boundary is located in the Malvinas trough, at the north of the BB and it would be transpressive (Cunningham et al., 1998; Giner-Robles et al., 2003; Bry et al., 2004). The change of the tectonic regime (transtensional to the W to transpressional to the E) would occur at 63.5 ºW (Lodolo et al., 2003; Yagupsky et al., 2003). As part of a study of the evolution of the SW Atlantic continental margin, we analyze and describe the morpho-structure of the western sector of the North Scotia Ridge.